Amphibian Hormones, Calcium Physiology, Bone Weight, and Lung Use Call for a More Inclusive Approach to Understanding Ossification Sequence Evolution - Rose, Christopher S. (Frontiers in Ecology and Evolution, 2021)
Skeleton plays a huge role in understanding how vertebrate animals have diversified in phylogeny, ecology and behavior. Recent evo-devo research has used ossification sequences to compare skeletal development among major groups, to identify conserved and labile aspects of a sequence within a group, to derive ancestral and modal sequences, and to look for modularity based on embryonic origin and type of bone. However, questions remain about how to detect and order bone appearances, the adaptive significance of ossification sequences and their relationship to adult function, and the utility of categorizing bones by embryonic origin and type. Also, the singular focus on bone appearances and the omission of other tissues and behavioral, ecological and life history events limit the relevance of such analyses. Amphibians accentuate these concerns because of their highly specialized biphasic life histories and the exceptionally late timing, and high variability of their ossification sequences. Amphibians demonstrate a need for a whole-animal, whole-ontogeny approach that integrates the entire ossification process with physiology, behavior and ecology. I discuss evidence and hypotheses for how hormone mediation and calcium physiology might elicit non-adaptive variability in ossification sequence, and for adaptive strategies to partition larval habitats using bone to offset the buoyancy created by lung use. I also argue that understanding plasticity in ossification requires shifting focus away from embryonic development and adult function, and towards postembryonic mechanisms of regulating skeletal growth, especially ones that respond directly to midlife environments and behaviors.